PENGARUH UPAH, KESEMPATAN KERJA, TINGKAT PENDIDIKAN DAN UMUR TERHADAP KEPUTUSAN MOBILITAS PULANG-BALIK (COMMUTING) TENAGA KERJA KABUPATEN KAMPAR KE KOTA PEKANBARU - Edinur Ilham (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to analyze the effect of the difference in wages, job opportunities, education level, age, marital status, number of family, and distance dependents simultaneously, partially, and the variables that most dominantly influence the decision to do a roundtrip migration of workers from Kampar to Pekanbaru City. The data used in this study are primary data obtained by conducting a direct survey to the research area and conducting interviews based on a questionnaire that has been compiled to 100 eligible respondents using a logistic regression model. The location of this research is the Kampar-Pekanbaru Border (SPBU before UIN SUSKA RIAU), Jalan Garuda Sakti Km 4, the main community access from Tapung District, Kampar Regency, Pekanbaru Pandau Trans Metro Terminal (Jl. Pandau Raya) which is the main access to Pekanbaru City and Kampar Regency (Siak Hulu District). The independent variable in this study is the variable wages, job opportunities, education level, age, while the dependent variable is the labor decision to do round-trip migration. The results of the study found that with a significance level of 5%, there is at least one independent variable that is statistically significant in influencing the dependent variable with an LR value of 87.11 and a p-value or prob chi2.